Tourism-Based Analysis and Development Potentials in Hortobágy - Tikász, Edit Ildikó (Acta Agraria Debreceniensis, 2004)
Tourism – especially ecotourism and health-tourism – could be one of the sectors which could make Hungary economically competitive after joining the European Union, by ensuring thousands of people employment possibilities, if they take advantage of local and regional opportunities. For this reason, it would be necessary to analyse the two types of tourism mentioned above, as well as to collect data and especially impressions concerning how these potentially lucrative sectors could best be structured and managed, as well as to predict their probable effects. The most important objectives of my study are to introduce the values of Hortobágy, to analyse the present status of tourism in the Hortobágy National Park, and to make suggestions for increasing the numbers of tourists, by making Hortobágy more attractive. As a resident of Debrecen, I visited the region several times and took part in programs at Hortobágy as well. I was always curious how the trip to the Hortobágy could be made more enjoyable. My research was carried out with the help of questionnaires, which were made in three languages – Hungarian, English and German –. In August 2002, I approached foreign and Hungarian tourists in Hortobágy village, and asked them to fill them in. To evaluate the questionnaires, I used Microsoft Excel ’00. During the evaluation, I calculated distribution, arithmetic mean and deviation. Moreover, I obtained the level of significance. My assumption that tourists visiting Hortobágy are “one-day” tourists, who are visiting the Hungarian Pusta because of an actual program, was supported by my research. I must emphasise that mostly passive tourism opportunities are offered in Hortobágy, where tourist are only external observers of the programs. In order to change this situation, I suggested that visitors to Hortobágy can be encouraged to stay longer by offering them various programs, in which tourists are actively involved. My program recommendations include a craftsman’s house or tent, where the visitors can try to make typical folk instruments. Moreover, I made suggestions as to how to teach tourists to make Hungarian dishes. I also outlined several one-day program possibilities. Among the opportunities, I also mentioned the need to provide tourists possibilities to spend several days in a conventional Pusta life-style. To realise these things adequate infrastructure and information system should be developed.